Exposure to environmental toxicants reduces global N6-methyladenosine RNA methylation and alters expression of RNA methylation modulator genes - Cayir, Akin; Barrow, Timothy M.; Guo, Liqiong; Byun, Hyang-Min (Environmental research, 2019)
The epitranscriptome comprises more than 100 forms of RNA modifications. Of these, N6-methyladenosine (m6A) is the most abundant form of RNA methylation, with roles in modulating mRNA transcript processing and regulation. The aims of the study were to examine changes in m6A RNA methylation in A549 lung epithelial cells in response to environmental toxicants, and differential gene expression of m6A modulator genes (‘readers’, ‘writers’ and ‘erasers’) in human subjects exposed to particulate matter (PM) and in lung cancer tissue using publicly-available microarray datasets. Global m6A methylation levels were measured in total RNA after exposure to two carcinogens (PM and sodium arsenite) for 24- and 48-h, and to two endocrine disruptors (bisphenol A and vinclozolin) for 24-h. Global m6A methylation level significantly decreased with exposure to >62 μg/ml PM, >1 μM sodium arsenite, >1  μM bisphenol A (BPA), and 0.1  μM vinclozolin. In an analysis of a published dataset derived from a population study, we observed that m6A writers (METTL3 and WTAP), erasers (FTO and ALKBH5) and readers (HNRPC) showed significantly higher expression among participants in the high-PM2.5 exposure group compared to those in the low-exposure control group (all p < 0.05). Further, the m6A writer METTL3 shows reduced expression in lung tumors in comparison to normal lung epithelia (p < 0.0001). Our findings reveal that m6A RNA methylation can be modified by exposure to environmental toxicants, and exposure to particulate matter is associated with differential expression level of m6A RNA methylation modification machinery. •Alterations in m6A RNA methylation in A549 cells with environmental exposures.•Global m6Adecreasedwithparticulate matter, arsenite, BPA & vinclozolin exposure.•Expression of METTL3, WTAP, FTO, ALKBH5, and HNRPC increased with particulate matter exposure.•Expression of the m6A writerMETTL3 is lower in lung tumors than normal tissue.